2022
DOI: 10.31599/jsrcs.v3i1.1165
|View full text |Cite
|
Sign up to set email alerts
|

Sistem Pendukung Keputusan Untuk Penentuan Siswa Teladan Menggunakan Metode Weighted Product

Abstract: Setiap sekolah akan menentukan siswa teladan setiap akhir semester untuk mengukur uji kompetensi setiap siswa. Namun dalam menentukan siswa teladan di sekolah selalu menimbulkan perdebatan antar dewan guru karena setiap dewan guru mempunyai pilihan masing masing untuk di jadikan siswa teladan dalam sekolah. Sistem Pendukung Keputusan (SPK) atau Decision Support System (DSS) merupakan suatu sistem informasi yang ditujukan untuk membantu sekolah dalam memecahkan masalah penentuan siswa teladan. Salah satu metode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
(6 reference statements)
0
0
0
Order By: Relevance
“…The resulting system uses one of the decision support system methods, namely the weighted product. It is found that it provides objective, effective, efficient calculation results that can also be accurate based on the results of calculations performed manually using Excel software and automatic calculations using a system that generated from this research [5].…”
Section: Introductionmentioning
confidence: 98%
“…The resulting system uses one of the decision support system methods, namely the weighted product. It is found that it provides objective, effective, efficient calculation results that can also be accurate based on the results of calculations performed manually using Excel software and automatic calculations using a system that generated from this research [5].…”
Section: Introductionmentioning
confidence: 98%